2011
DOI: 10.1371/journal.pone.0018115
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Splicing and Nonsense-Mediated RNA Decay Contribute to the Regulation of SHOX Expression

Abstract: The human SHOX gene is composed of seven exons and encodes a paired-related homeodomain transcription factor. SHOX mutations or deletions have been associated with different short stature syndromes implying a role in growth and bone formation. During development, SHOX is expressed in a highly specific spatiotemporal expression pattern, the underlying regulatory mechanisms of which remain largely unknown. We have analysed SHOX expression in diverse embryonic, fetal and adult human tissues and detected expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 39 publications
0
36
0
Order By: Relevance
“…SHOXa is expressed in numerous tissues, including skeletal muscle, placenta, heart and bone marrow fibroblasts, among others; SHOXb expression is more restricted and is predominantly found in fetal kidney, skeletal muscle and bone marrow fibroblasts 28. Durand et al 29 also reported SHOXa and SHOXb expression in different fetal and adult human brain regions, including fetal hindbrain, thalamus and basal ganglia, and adult thalamus, cerebellum and frontal cortex, pointing to an additional function of SHOX during fetal brain development and maintenance of brain function. The same study also identified novel SHOX exons (2a, 7–1, 7–2 and 7–3), which create new coding and untranslated regions, resulting in at least four novel SHOX splice variants.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…SHOXa is expressed in numerous tissues, including skeletal muscle, placenta, heart and bone marrow fibroblasts, among others; SHOXb expression is more restricted and is predominantly found in fetal kidney, skeletal muscle and bone marrow fibroblasts 28. Durand et al 29 also reported SHOXa and SHOXb expression in different fetal and adult human brain regions, including fetal hindbrain, thalamus and basal ganglia, and adult thalamus, cerebellum and frontal cortex, pointing to an additional function of SHOX during fetal brain development and maintenance of brain function. The same study also identified novel SHOX exons (2a, 7–1, 7–2 and 7–3), which create new coding and untranslated regions, resulting in at least four novel SHOX splice variants.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the genomic region downstream of SHOX2 harbours a highly conserved non-coding sequence homologous to the SHOX enhancer CNE5, which has been found to function primarily as a neural enhancer 36. Intriguingly, expression analysis in chicken embryos has revealed that Shox and Shox2 expression patterns overlap only partially in the developing chicken limb, whereas Shox expression is completely covered by Shox2 expression in the developing chicken brain 29. Consistent with these findings, it has been speculated that SHOX2 may partly take over the functions of SHOX in the neural tissues of cases with SHOX haploinsufficiency, mitigating the effects on neurodevelopment 29…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…43 Case II.5, with a terminal de novo 15q deletion located 1.5 Mb downstream of IGF1R and 244 kb downstream of the ADAMTS17 locus on the reverse strand, had a normal birth size, but showed proportionate progressive growth failure (SH/H ratio þ 1.58 SDS) with a normal head circumference. Clinical characteristics included slight frontal bossing of the skull, a high pitched voice and slight abdominal adiposity and delayed bone age.…”
Section: Discussionmentioning
confidence: 99%
“…Three recently published articles on miRNA regulations describe the utilization of miRWalk and TargetScan predictions in copy number variants [56], different splice variants of a gene [57] and single nucleotide polymorphisms (SNP) [53]. …”
Section: Applications Of Most Relevant Resourcesmentioning
confidence: 99%